Analyzing Exercises in An English Textbook Entitled 'Think' (CEFR A1) Based on Communicative Language Teaching - Wibowo, Enggar Pangesti; Wirza, Yanty (Journal of Foreign Language Teaching and Learning, 2000)
Background: Recent studies found that some English textbooks do not support Communicative Language Teaching (CLT) principles that are suitable to be emphasised in teaching with the current emancipated curriculum in Indonesia. Objective: This study attempts an analysis on exercises in an English textbook entitled “Think” (CEFR A1) by Cambridge University Press for seventh graders. The research was to analyze the extent to which the exercises in the textbook follow the principles of CLT, to explore the teachers’ perspective in the use of textbooks to support CLT, and to describe the students' performances of the communicative classroom activities. Methods: The research used a qualitative case study method employing document analysis, teachers’ interview and classroom observations in a private Islamic Junior High School in Semarang, Central Java. Findings: The results show that the textbook strongly promotes communicative competence dominated by task completion activities with a proportion of individual tasks excelling in pair/group works in them. Conclusion: However, the large number of exercises makes this book seem like a workbook. Although the teachers have adequate understanding of CLT principles and the activities presented in the textbook, the interviews showed that time constraints meant that most of the time, they could only use task completion and role play. The results of the students' performance showed that most of them succeeded in practicing the role play well although the low achievers who had problems in practicing the dialogue needed better scaffolding and time during the tasks completion.